A cultura do material escolar : desvelando a formatação da Instrução de Primeiras Letras na Província de Sergipe (1834-1858) - Lima, Gláriston dos Santos (2007)
This work is aimed at analising uses and functions of material culture of school that there was is first letters learning in Sergipe province, during the Emperor, for urderstanding its organization process, in 1834 1858 period. We sought for examining its shape, universe, valve, acquisition ways, and utilization, as of practices of teachers and methods of learning. We approached themes as: the representation of culture of school, the organization of primary leaming, the roll of educational legislation, the valves and conceptions of this education and the presence of materials in the pedagogical action of teachers that period. The aim was to estabelish an ampler sense about this study object, by permitting to understand is intervention on the first letter leaning organization during the emperor in Sergipe Province.